Invoking Alphonse: The founder figure as a historical resource for organizational identity work. Issue 12 (December 2018) - Basque, Joëlle; Langley, Ann
There has been growing interest in the rhetorical use of history to express organizational identity claims. Yet the evolving role of the founder figure in managerial accounts has not so far received specific attention. In this study, we examine how the founder figure is used to articulate, enact, stretch, preserve or refresh expressions of organizational identity, drawing on an 80-year magazine archive of a financial cooperative. We identify five modes of founder invocation, and show how distance from founding events leads to increasing abstraction in linkages between the founder and organizational identity claims. The paper offers a dynamic perspective on the mobilization of the founder in organizational identity construction as well as an understanding of how and why founders may remain established identity markers long after their demise.